Análisis de tecnologías para el tratamiento de aguas de producción de la industria de hidrocarburos y su potencial uso en sistemas de riego (2023)
The present work focused on the analysis of the technologies available for the treatment of hydrocarbon production water for its subsequent use in irrigation systems. First, a general definition of these waters was made, where their possible origins, general components, and viable disposal options were identified. In the same way, a more specific characterization was carried out on the components and contaminants that production waters may present; These include total dissolved solids, inorganic ions, organic compounds, petroleum hydrocarbons, COD and BOD, metals, radioactive materials, and added chemicals.